Mandibular asymmetry in radiographies from non-syndromic children with and without cleft lip and palate in Bucaramanga, Colombia. - La Rosa, Javira La Rosa (2021)
Objective: assess any difference in growth and development of mandible in radiographs from cleft lip and/or palate patients. Methods: an analytical cross-sectional study was conducted with a sample of 130 panoramic and cephalic radiographies from patients who attended the orthodontic service at Universidad Santo Tomás. Sixty-four (49.2%) men and 66 (50.8%) women with an average age of 10.6 ± 3.1 years were assessed. Anatomical points were defined on the radiographies and the measurements were performed in the two groups. The Student t-test and the multivariate ANOVA analysis were applied.  A p<0.05 was considered as statically significant.  Results: a statistically significant difference was found in the symmetry of patients with cleft lip and palate (p=0.0340), as well as a lower height of the left branch represented by the cephalometric plane Co-Inc (p=0.0414) and the mandibular body by Co – Gn (p=0.0094) and Go - Pog (p=0.0015). Conclusions: the size of the mandibular body represented by the measurements taken in panoramic and lateral cephalic radiographs (Go-Pog, Co-Gn) of patients with cleft lip and palate is smaller than that of patients without clefts.